2023
DOI: 10.57257/japm-d-22-00011
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of invasive floating fern leads to rapid recovery of ecological functions in coastal fresh water wetlands in Louisiana

Steven Woodley,
Charles Wahl,
Alexander Tryforos
et al.

Abstract: Despite the success of the salvinia weevil (Cyrtobagous salviniae) at controlling giant salvinia (Salvinia molesta), its impact on the timing of reduction of giant salvinia cover and recovery of submerged aquatic vegetation (SAV) and dissolved oxygen remains unknown. A two-year field study (2016 to 2017) was conducted in coastal wetlands in southwestern Louisiana to measure the impact of biological control of giant salvinia. Water temperature, dissolved oxygen, weevil densities, and giant salvinia and SAV cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…As we predicted, the warm temperatures and longer growing season of Puerto Rico allowed the weevil to establish, grow, and ultimately control salvinia. This success is similar to biological control programs implemented in tropical and subtropical regions of United States, South Africa, Senegal, and Australia [17,[46][47][48][49][50]. The air temperatures of Las Curias fluctuate between 23 and 30 • C during winter and summer, respectively, matching near perfect conditions for the weevil's adult feeding, dispersal (flight and walking), reproduction (mating, oviposition), and larval development [51][52][53][54].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As we predicted, the warm temperatures and longer growing season of Puerto Rico allowed the weevil to establish, grow, and ultimately control salvinia. This success is similar to biological control programs implemented in tropical and subtropical regions of United States, South Africa, Senegal, and Australia [17,[46][47][48][49][50]. The air temperatures of Las Curias fluctuate between 23 and 30 • C during winter and summer, respectively, matching near perfect conditions for the weevil's adult feeding, dispersal (flight and walking), reproduction (mating, oviposition), and larval development [51][52][53][54].…”
Section: Discussionsupporting
confidence: 61%
“…This makes us wonder about a weevil density at which there is a point of no recovery of salvinia, or a putatively tipping point where the damage is so severe that salvinia collapsed and sunk. Future studies should aim to understand the relationship among weevil densities, nutrient load, and growth rates of salvinia [17]. Finally, sampling towards the end of the project (2022) revealed that weevils did not extirpate salvinia from the reservoir, but rather weevils and salvinia reached an equilibrium at lower densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation